2021
DOI: 10.3390/s21082724
|View full text |Cite
|
Sign up to set email alerts
|

Time-Efficient Convolutional Neural Network-Assisted Brillouin Optical Frequency Domain Analysis

Abstract: To our knowledge, this is the first report on a machine-learning-assisted Brillouin optical frequency domain analysis (BOFDA) for time-efficient temperature measurements. We propose a convolutional neural network (CNN)-based signal post-processing method that, compared to the conventional Lorentzian curve fitting approach, facilitates temperature extraction. Due to its robustness against noise, it can enhance the performance of the system. The CNN-assisted BOFDA is expected to shorten the measurement time by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This has the advantage that no ultra-fast electronics are required, which, on the one hand, has a positive impact on the system's cost but, on the other hand, increases the measurement time significantly. For this reason, a machine learning method for time-efficient BOFDA measurements was proposed [69,167].…”
Section: Machine Learning Applied In Brillouin Frequency Domain Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has the advantage that no ultra-fast electronics are required, which, on the one hand, has a positive impact on the system's cost but, on the other hand, increases the measurement time significantly. For this reason, a machine learning method for time-efficient BOFDA measurements was proposed [69,167].…”
Section: Machine Learning Applied In Brillouin Frequency Domain Sensorsmentioning
confidence: 99%
“…Specifically, machine learning algorithms have been employed to enhance the measurement accuracy and shorten the signal processing time without increasing the system's cost [40,66,67]. Machine learning has also contributed to enhanced spatial resolution in BOTDA systems [68] and shorter measurement times in BOFDA systems [69]. Furthermore, the problem of temperature and strain cross-sensitivity has been addressed using machine learning in both BOTDA and BOFDA systems [70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the strain and temperature can be indirectly measured through BOFDA technology. Compared with other distributed fiber optic sensing technologies, the advantages of BOFDA are its high precision and high resolution [24]. The testing accuracy of BOFDA can reach 2 µε or 0.1 • C, its spatial resolution can reach 0.2 m, its dynamic range can exceed 20 dB, and a distributed fine decomposition of strain and temperature can be realised.…”
Section: Bofda Pipeline Leak Testing Principlementioning
confidence: 99%
“…Practice has shown that correlation methods are quite effective in studying signals with low SNR. Another noteworthy method is machine learning [ 34 , 35 , 36 , 37 ]. These are artificial intelligence methods used to obtain the correct characteristic feature which is not a direct solution to the problem but is a learning input through applied solutions to many other similar problems.…”
Section: Introductionmentioning
confidence: 99%